2019
DOI: 10.7567/1347-4065/ab0baf
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of porous γ-Fe2O3 via alkaline treatment of size controlled scorodite particles synthesized using ultrasound irradiation and its evaluation as a cathode for lithium-ion battery

Abstract: Herein, we synthesized scorodite particles using ultrasound irradiation in a strong sulfuric acidic solution (pH 0.5) and investigated the scorodite particles' size and morphology. The highest crystallinity of scorodite (96%) was synthesized using 200 kHz ultrasonic treatment, and maximum yield of scorodite was obtained in three conditions: 200, 28 kHz, and stirrer. The oxidant generated through 200 kHz ultrasound irradiation enhanced Fe(II) oxidation in the solution resulting in crystal nuclei formation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…In our previous report, the arsenic leaching test results of highly crystalline (96%) clustered scorodite particles synthesized at pH 0.5 using 200 kHz ultrasound indicated an elution level of 29 ppm. 16) The amount of arsenic eluted from the scorodite obtained using ultrasound at pH 1.0 was smaller than this amount. This can be due to the scorodite's higher crystallinity, which enhanced the low solubility.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…In our previous report, the arsenic leaching test results of highly crystalline (96%) clustered scorodite particles synthesized at pH 0.5 using 200 kHz ultrasound indicated an elution level of 29 ppm. 16) The amount of arsenic eluted from the scorodite obtained using ultrasound at pH 1.0 was smaller than this amount. This can be due to the scorodite's higher crystallinity, which enhanced the low solubility.…”
Section: Resultsmentioning
confidence: 91%
“…Maghemite made from clustered scorodite has the same initial discharge capacity as maghemite made from clustered amorphous iron arsenate (FeAsO 4 ), which was previously reported (161 mAh g −1 ). 16) Therefore, it was observed that the presence or absence of crystal water in scorodite had no effect on the battery performance of maghemite deposited by alkaline treatment. Furthermore, the battery performance of maghemite obtained in this study was compared with the reported values.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations